2015
DOI: 10.4055/cios.2015.7.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Combined Shelf Acetabuloplasty with Femoral Varus Osteotomy in Severe Legg-Calve-Perthes (LCP) Disease: Advanced Containment Method for Severe LCP Disease

Abstract: BackgroundStandard treatments may provide adequate containment in mild to moderate Legg-Calve-Perthes disease (LCPD), but they can be problematic in more severe cases. The purpose of this study was to report the results of combined shelf acetabuloplasty with femoral varus osteotomy in severe LCPD.MethodsWe reviewed 12 patients who had undergone combined shelf acetabuloplasty with femoral varus osteotomy. The indications for this type of operation were: (1) above 8 years of age at clinical onset; (2) massive fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Four articles looked at FVO [ 17 , 18 , 19 , 22 ], two articles evaluated the combination of FVO + Salter osteotomy [ 23 , 26 ], eight articles examined lateral shelf acetabuloplasty [ 20 , 24 , 27 , 28 , 29 , 33 , 36 , 37 ], two articles addressed arthrodiastasis [ 25 , 30 ], tow articles analyzed the Salter osteotomy [ 34 , 39 ], and two articles described the rotational transtrochanteric osteotomy [ 31 , 32 ]. Finally, one article analyzed the Chiari osteotomy [ 21 ], one the triple osteotomy [ 38 ], and one the combination of shelf acetabuloplasty + FVO [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four articles looked at FVO [ 17 , 18 , 19 , 22 ], two articles evaluated the combination of FVO + Salter osteotomy [ 23 , 26 ], eight articles examined lateral shelf acetabuloplasty [ 20 , 24 , 27 , 28 , 29 , 33 , 36 , 37 ], two articles addressed arthrodiastasis [ 25 , 30 ], tow articles analyzed the Salter osteotomy [ 34 , 39 ], and two articles described the rotational transtrochanteric osteotomy [ 31 , 32 ]. Finally, one article analyzed the Chiari osteotomy [ 21 ], one the triple osteotomy [ 38 ], and one the combination of shelf acetabuloplasty + FVO [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…24 another study in Korea showed different results, out of 12 patients revealed Stulberg gradeI, 0 cases; Stulberg grade II, 4 cases (34%); Stulberg III, 7cases (58%); Stulberg IV, 1 case (8%); and Stulberg V, 0 cases. 10 Our study showed that more than half of the cases had a central edge angle of 26º-40º followed by those having ≤ 25º and those with > 40º (31.8% & 9.1%, respectively). This is inconsistent with results of a study in Korea, where the mean angular correction of the varus osteotomy in group A was 20° and the mean medial displacement was 21%, the angular correction of valgus osteotomy in group B was 28°, and lateral displacement was 41%.…”
mentioning
confidence: 52%
“…The characteristics of the included studies [1,9,10,32,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] are reported in Multimedia Appendix 1.…”
Section: Overviewmentioning
confidence: 99%